Human capital in the context of high levels of inequality in South Africa - Friderichs, Tamaryn Jean (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Piketty's (2014) book titled "Capital in the Twenty-First Century" sparked widespread interest in global inequality, the distinction between wealth and income inequality and the economic, social and political processes accounting for changes in economic inequality over time. Piketty's (2014) study controversially stated that widening economic inequality is the normal state of affairs in capitalist societies. The return from capital/wealth (terms used interchangeably) will almost always outpace the returns from labour. In contrast with Piketty's (2014) thesis that the returns on non-human capital drive growing income inequality, economists such as Leibbrandt et al. (2012), Van der Berg (2014) and Hundenborn et al. (2016) have found that the labour market and human capital (HC) are the primary sources of income inequality. The research problem for this study stems from these contrasting views.
Keywords: Human capital -- South Africa; Income distribution -- South Africa; Labor market -- South Africa; Latent variables; Confirmatory factor analysis; Education Economic aspects -- South Africa